Overwintering of Rabies Virus in Silver Haired Bats (Lasionycteris noctivagans). - April D Davis; Shannon M D Morgan; Michelle Dupuis; Craig E Poulliott; Jodie A Jarvis; Rhianna Franchini; Anne Clobridge; Robert J Rudd (PLoS ONE)
Silver-haired bats, (Lasionycteris noctivagans) are semi-colonial, migratory tree bats that have infrequent contact with humans. Despite the species rarity, the L. noctivagans rabies variant is the most commonly reported rabies virus variant (RABV) in domestically acquired human rabies cases in the US. Unlike big brown bats (Eptesicus fuscus) and little brown bats (Myotis lucifugus), L. noctivagans are not considered true hibernators. It is unknown if RABV can overwinter in hibernating L. noctivagans or is only maintained in members of this taxa that migrate to warmer climates. To better understand RABV overwintering in this species, L. noctivagans were inoculated intramuscularly with either a homologous RABV (L. noctivagans Virus 1) or one of two heterologous RABV (Eptesicus fuscus Virus 2 and Myotis lucifugus Virus 1). Five days following inoculation, L. noctivagans were placed in a hibernation chamber for 6 weeks. Our results demonstrate that rabies virus can overwinter in L. noctivagans yet the incubation period was extended 6 weeks when compared to bats maintained at ambient temperatures. Additionally, we found that the longer the incubation period, the greater the viral dissemination to the salivary glands. Similar to our previous studies, L. noctivagans were most susceptible to a homologous variant. In summary, we found that RABV incubation is extended following a subcutaneous exposure or maintenance in hibernation and longer incubation times increase dissemination and potential for transmission.